ANALISIS YURIDIS TANGGUNG JAWAB AHLI WARIS TERHADAP HUTANG PEWARIS MENURUT HUKUM ISLAM DAN HUKUM PERDATA - REZA BOBOY ARYAGUNA (PREMISE LAW JURNAL, 2019)
Dosen Pembimbing:1. Prof. Dr. H.M. hasballah Thaib, MA, PhD2. Prof. Dr. Muhammad Yamin, SH, MS, CN3. Zamakhsyari Bin Hasballah Thaib, MA, PhD A debt which has to be paid off in its due time to the person who gives the loan so that it will effect his property because the testator has to paid off his debt. In the Islamic concept, a dead person will not be the burden of his heirs since debt is not bequeathed. It is the responsibility of the dead person, relating to his property. An heir is responsible only for paying off the debt from the existing property. The research used the theory of justice with judicial normative approach, by analyzing deeply legal provisions, jurisprudence, and the opinions of legal experts. The data were gathered by conducting library research. On the other hand, Article 833, paragraph 1 of the Civil Code requires an heir to pay off the whole debt, will, and others left by a testator.Keywords: Juridical Analysis, Responsibility, Debt